2011
DOI: 10.1002/j.1556-6676.2011.tb02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Muslim Americans: Cultural and Spiritual Assessments

Abstract: In this article, the authors identify the cultural and spiritual assessments needed to conduct counseling with Muslim Americans and Muslim immigrants to the United States. Assessment processes are outlined that include cultural identity (which subsumes several variables); worldview; spiritual assessment along with acculturation level and migration concerns; impact of languages spoken; social, occupational, and educational status of the client in host culture and in home culture (if the client is an immigrant);… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
0
22
0
1
Order By: Relevance
“…Ibrahim and Cass (2011) revealed that the success in acculturation process of Arab immigrants depends on the level to which they stick to the religious traditions and the character of religion as well (p. 388). Islam, as with other world religions, contains different interior movements distinctive from each other in beliefs, traditions, norms, and values.…”
Section: Overview Of Acculturation Process Specific To Arab-muslim Immentioning
confidence: 99%
See 1 more Smart Citation
“…Ibrahim and Cass (2011) revealed that the success in acculturation process of Arab immigrants depends on the level to which they stick to the religious traditions and the character of religion as well (p. 388). Islam, as with other world religions, contains different interior movements distinctive from each other in beliefs, traditions, norms, and values.…”
Section: Overview Of Acculturation Process Specific To Arab-muslim Immentioning
confidence: 99%
“…Islam, as with other world religions, contains different interior movements distinctive from each other in beliefs, traditions, norms, and values. Such differences, according to Ibrahim and Cass (2011), play an immense role in the future process of acculturation, where more radical Islamic views hinder the process of acculturation (p. 389).…”
Section: Overview Of Acculturation Process Specific To Arab-muslim Immentioning
confidence: 99%
“…For example, Ibrahim and Dykeman (2011) argued that the American Psychiatric Association requires a "cultural formulation [understanding of client cultural identity and context] to be completed with a client before a diagnosis is given" (Ibrahim & Dykeman, 2011, p. 387). According to this view point, any treatment provided a client requires sensitive attention to the cultural norms of that individual.…”
Section: Upr As a Culturally-normative Constructmentioning
confidence: 99%
“…The Muslim population in each region has incorporated Islam as a religion, within their ongoing tribal and historical cultures; a clear-cut definition of people following Islam would be that they believe in one God, and accept all the prophets who introduced the Ten Commandments, the Torah, the Bible, and finally the Quran. Currently the Muslim population in the United States is highly diverse, and involves 75 or more ethnicities or nationalities (Ibrahim & Dykeman, 2011;Maloof & Ross-Sheriff, 2003). There is considerable diversity in the manner Islam is practiced, due to cultural interpretations across cultures and various branches of Islam.…”
mentioning
confidence: 99%